The Science of Persuasion: Cialdini’s Principles in Shaping Purchase Decision on Shopee Indonesia - Izara Ridwan; Lila Maria Kaban (Universitas Pelita Harapan, 2025)
This study investigates whether Cialdini’s principles of persuasion – Reciprocity, Social Proof, and Liking – affect consumer purchasing decisions on the Shopee application in Indonesia. Amidst the rapid growth of e-commerce and intense competition among online platforms, understanding the psychological and social factors influencing consumer behavior is increasingly vital. While previous studies have explored general online buying behavior, few have focused specifically on Shopee Indonesia using Cialdini’s persuasive strategies. This quantitative research used a purposive sampling technique to gather data from 100 Shopee users who had made at least two purchases. Data was collected via an online questionnaire and analyzed using multiple linear regression. The results show that Social Proof and Liking have a significant and positive effect on purchasing decisions, while Reciprocity does not when tested independently. However, when analyzed simultaneously, all three variables significantly affect purchasing decisions, with a combined explanatory power of 73.5%. The findings highlight the importance of emotional and social strategies in enhancing digital marketing effectiveness and recommend Shopee prioritize influencer engagement and consumer review visibility.